Equilibrium, Kinetics, and Thermodynamic Studies of Malachite Green Adsorption onto Fig (Ficus cartia) Leaves - Yemane Tadesse Gebreslassie (Journal of Analytical Methods in Chemistry)
The release of dyes from dying industries such as leather, paper, and textiles is an important cause of environmental pollution. In the present study, the batch adsorption measurements were carried out using stimulated aqueous solutions and the effect of operating variables such as initial malachite green concentration, amount of adsorbent, solution pH, contact time, and solution temperature, were investigated. The experimental result showed that the percentage removal decreased with an increase in initial dye concentration but increased as pH of the solution, contact time, and adsorbent dose increased. The equilibrium data were analyzed using Langmuir adsorption isotherm, Freundlich adsorption isotherm, and Tempkin isotherm models, and it was observed that the Langmuir adsorption isotherm better described the adsorption process. The monolayer adsorption capacity of activated carbon prepared from fig leaves for malachite green adsorption was found to be 51.79 mg/g at 298 K. Furthermore, the adsorption kinetics of the dye was investigated, and the rate of adsorption was found to follow the pseudo-first-order kinetic model with intraparticle diffusion as one of the rate-determining steps. The negative value of ΔG0 and the positive values of ΔH0 indicate the spontaneous and endothermic nature of the adsorption process, respectively. The experimental result obtained in the present study and comparison with other reported adsorbents indicate that activated carbon prepared from fig leaves could be used as a low-cost alternative adsorbent for the removal of malachite green from aqueous solution.